MAIN CAUSES, DIAGNOSIS, AND EFFECTIVE TREATMENT OF POSTCHOLECYSTECTOMY SYNDROME - Abduraimov Zafarjon; Ziyadulla Erkinovich Khidirov (Scholar Express Journals, 2023)
The paper presents the frequency and differences of opinions on the definition of postcholecystectomy syndrome. Four groups of the main causes responsible for the development of different clinical symptoms after cholecystectomy are distinguished. It is proved that pathogenesis of digestive disorders in postcholecystectomy syndrome is complex and multicomponent, includes the number of "crossing" closely connected pathogenic "rings". It is shown that in the absence of indications for surgical correction of the syndrome the optimal way to break the above described "vicious circles" is the prescription of pancreatin combination in the form of enterosolubilic minimicrospheres and selective myotropic antispasmodic agent mebeverine
Keywords: cholecystectomy; postcholecystectomy syndrome; common bile duct